2022
DOI: 10.1155/2022/7547043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Adult Cataract in the Jingan District of Shanghai

Abstract: Purpose. We report the prevalence of age-related cataract (ARC) in the Jingan district of Shanghai and analyze the risk factors for ARC to be better prepared for the increasing burden of cataracts as a significant cause of visual impairment worldwide. Methods. From March to June 2010, a population-based, cross-sectional study was conducted in a community selected by stratified cluster sampling in the Jingan district of Shanghai. Residents aged 40 and older were recruited and investigated by questionnaires and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Estrogen also functions as a protective hormone against oxidative stress which is related to lens opacification. 2,3 In this study, there were more men underwent cataract surgery with a ratio of 54.26% and 45.7% to women. This is consistent with a study conducted by Fang et al although 60% of cataract patients are women, men are 1.39 times more likely to undergo cataract surgery than women.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Estrogen also functions as a protective hormone against oxidative stress which is related to lens opacification. 2,3 In this study, there were more men underwent cataract surgery with a ratio of 54.26% and 45.7% to women. This is consistent with a study conducted by Fang et al although 60% of cataract patients are women, men are 1.39 times more likely to undergo cataract surgery than women.…”
Section: Discussionmentioning
confidence: 65%
“…Worldwide cataract prevalence is dominated by women. 3 Older age and lower socioeconomic status are associated with greater differences in cataract incidence by sex. 9 There is also a decrease in estrogen hormone in women during menopause which increases the risk of cataracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience demonstrated a significant incidence of grade 3 cataracts, often bilateral, which could be due to a cohort with a median age of 76 years at diagnosis, corresponding to a baseline risk of age-related cataracts over 40% [ 11 , 12 ]. The available dosimetric data did not allow for correlation analysis in this study, but considering the low median dose at 0.1cc of the lens, the authors express reservations about affirming a clear association between the administered treatment and the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract is the leading cause of reversible blindness and visual impairment worldwide [1], including Poland [2,3]. Epidemiological studies have shown that cataract results from multiple contributing factors [1,4,5,6,7,8,9,10,11,12,13,14,15]. Risk factors for, and causes of, cataract include ageing, genetics, lifestyle exposure, behaviors, infections, various health conditions, and socioeconomic factors [1,4,5,6,7,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%